2022
DOI: 10.1002/ctm2.930
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis‐related gene signature is enriched in cancer‐associated fibroblasts in the stem‐like subtype of gastric cancer

Abstract: related gene signature is enriched in cancer-associated fibroblasts in the stem-like subtype of gastric cancer Dear EditorPrognostic markers in gastric cancer 1 are not only used to clinically classify patients into groups but are also being studied extensively for assessing cancer progression and drug development. Hence, the mechanisms by which genes associated with different prognoses in gastric cancer affect stem-like molecular subtypes require further investigation. We selected the top 500 genes with signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In cohort 2, the stem-like signature was enriched in fibroblasts (Figure 1C). 3 We confirmed that 14 pathways were highly upregulated in stem-like tumour cells (Figure 1D). Furthermore, we identified differentially expressed genes (DEGs) by distinguishing tumour cells with highly stem-like signatures from others, as well as the most significantly enriched pathways: blood vessel development and NABA core matrix signalling (Figure 1E).…”
supporting
confidence: 68%
“…In cohort 2, the stem-like signature was enriched in fibroblasts (Figure 1C). 3 We confirmed that 14 pathways were highly upregulated in stem-like tumour cells (Figure 1D). Furthermore, we identified differentially expressed genes (DEGs) by distinguishing tumour cells with highly stem-like signatures from others, as well as the most significantly enriched pathways: blood vessel development and NABA core matrix signalling (Figure 1E).…”
supporting
confidence: 68%
“…We observed that the higher the abundance of fibroblasts was, the poorer the survival of patients with GC. The reason for this may be that the dense ECM forms a physical barrier that promotes tumor progression and prevents drug penetration [ 28 ]. As with the results of our analysis, fibroblast content can be utilized to predict prognosis, which has been validated in numerous tumors [ 29 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used a basic machine learning algorithm to perform feature selection and predict the ICB response in gastric cancer. The signature genes [33] have the advantage of predicting the ICB response of patients with gastric cancer and provide general insights for researchers to study the mechanism. We selected a signature gene that discriminates between the ICB responses for each algorithm using bulk and single-cell expression data.…”
Section: Discussionmentioning
confidence: 99%